2011
DOI: 10.4244/eijv6i7a144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on the clinical outcomes of coronary revascularisation for the treatment of patients with multivessel de novo coronary artery lesions: sirolimus-eluting stent vs. coronary artery bypass surgery and bare metal stent, insight from the multicentre randomised Arterial Revascularisation Therapy Study Part I (ARTS-I) and Part II (ARTS-II)

Abstract: Aims: We sought to evaluate the prognostic impact of age on the procedural results and subsequent clinical outcomes in patients with multivessel disease (MVD) treated either by coronary artery bypass surgery (CABG) or by percutaneous coronary intervention (PCI) with or without drug eluting stents, based on data of the Arterial Revascularisation Therapies Study (ARTS) part I and part II. The potential influence of age in determining the most appropriate revascularisation strategy for patients with MVD is largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
(27 reference statements)
0
10
1
Order By: Relevance
“…Previous studies have reported that LV dysfunction is an independent predictor of adverse mortality and MACE outcomes following PCI and we have observed a similar independent relationship between LV dysfunction and worsening MACE and mortality outcomes in our cohort, in all age groups studied. Older patients have a greater burden of co‐morbid conditions , are more likely to have multivessel disease and adverse lesion characteristics such as tortuosity and severe calcification and age itself is independently associated with worse MACE and mortality outcomes in patients undergoing PCI in some studies but not all and features strongly in risk stratification scores for mortality and MACE prediction in patients undergoing PCI .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that LV dysfunction is an independent predictor of adverse mortality and MACE outcomes following PCI and we have observed a similar independent relationship between LV dysfunction and worsening MACE and mortality outcomes in our cohort, in all age groups studied. Older patients have a greater burden of co‐morbid conditions , are more likely to have multivessel disease and adverse lesion characteristics such as tortuosity and severe calcification and age itself is independently associated with worse MACE and mortality outcomes in patients undergoing PCI in some studies but not all and features strongly in risk stratification scores for mortality and MACE prediction in patients undergoing PCI .…”
Section: Discussionmentioning
confidence: 99%
“…However, age, which emerged as a strong independent predictor of MACCE following CABG surgery (P <0.005), was not a predictor of adverse events following PCI. 100 Similarly, the SYNTAX score II algorithm also favours PCI for older patients. 109 Emerging evidence suggests that frailty is a better marker of biological age and more important than chrono logical age in determining the outcomes after PCI 116 or CABG.…”
Section: Chronic Kidney Diseasementioning
confidence: 98%
“…98 Conversely, diabetes was an independent predictor of outcomes after PCI, but not in CABG surgery, in the Australasian Society of Cardiac and Thoracic Surgeons and the Melbourne Interventional Group registry, 99 and in a combined post-hoc analysis of the ARTS-I and ARTS-II studies. 100 Two dedicated trials have shown a clear advantage of CABG surgery in patients with diabetes. The BARI 2D trial investigators enrolled 2,368 patients with type 2 diabetes and CAD who underwent either prompt PCI or CABG surgery with intensive medical therapy, or intensive medical therapy alone.…”
Section: Diabetesmentioning
confidence: 99%
“…In patients over the age of 75, life expectancy is sufficiently limited that the long-term prognostic benefits of CABG are not seen [7,33,34]. Therefore revascularisation should focus on the safe relief of symptoms.…”
Section: Advanced Agementioning
confidence: 99%